1980
DOI: 10.1152/ajpheart.1980.239.3.h427
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pentobarbital anesthesia on vulnerability to ventricular fibrillation

Abstract: Ventricular fibrillation threshold (VFT), frequently determined in dogs during pentobarbital sodium anesthesia, usually is replaced by a single repetitive extrasystole threshold (SRET) or a multiple repetitive extrasystole threshold (MRET) determination in conscious animals and in the human being. In the present study SRET, MRET, and VFT were determined initially in 39 pentobarbital sodium-anesthetized dogs. One week later these three thresholds were redetermined during anesthesia in 13 of the 39 dogs (control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Like pentobarbital, both ketamine and fentanyl are known to possess antiarrhythmic effects (Hoffmeister et al 1958, Laforet et al 1958, Olichney & Modell 1958, Dawson et al 1980, Thurmon & Tranquilli 1986, Hunt & Ross 1988, Smith et al 1997. However, in the present study, swine anaesthetized with medetomidineketamine-fentanyl showed a substantially higher incidence of ischaemia-induced ventricular brillation than swine anaesthetized with pentobarbital.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like pentobarbital, both ketamine and fentanyl are known to possess antiarrhythmic effects (Hoffmeister et al 1958, Laforet et al 1958, Olichney & Modell 1958, Dawson et al 1980, Thurmon & Tranquilli 1986, Hunt & Ross 1988, Smith et al 1997. However, in the present study, swine anaesthetized with medetomidineketamine-fentanyl showed a substantially higher incidence of ischaemia-induced ventricular brillation than swine anaesthetized with pentobarbital.…”
Section: Discussionmentioning
confidence: 99%
“…This agent possesses a cardiodepressive effect (Priano et al 1969, Sawyer et al 1971, Bailie et al 1979, Namba et al 1994, with increased re ex pressoreceptor activity (Manders & Vatner 1976), and an antiarrhythmic effect (Hoffmeister et al 1958, Laforet et al 1958, Olichney & Modell 1958, Dawson et al 1980, Hunt & Ross 1988. Because these effects are dosedependent (Nattel et al 1990, Namba et al 1994, the smallest dose to achieve general anaesthesia is usually chosen.…”
mentioning
confidence: 99%
“…It is also a membrane depressant on myocytes and reduces the responsiveness of these cells to sympathetic stimulation, thus having some kind of antiarrhythmic effect(12). Indeed, Siegmund et al(6) demonstrated that during pentobarbitone anaesthesia, compared to conscious animals, a significantly lower number of animals developed irreversible ventricular fibrillation during the first twenty minutes of myocardial infarction.Dawson et al(13) have shown that pentobarbitone affects the ventricular fibrillation threshold in dogs thus influencing the vulnerability of the myocardium to ventricular fibrillation.…”
mentioning
confidence: 99%
“…DAWSON et coIl. (3) have shown that pentobarbital anesthesia increases the threshold for electrically induced VF. We therefore believe that pentobarbital anesthesia decreases the vulnerability for CM induced VF, thus our canine model probably overestimates the contact time required for CM induced VF in the awake animal.…”
Section: Discussionmentioning
confidence: 99%